Visualization of Light Elements using 4D STEM: The Layered‐to‐Rock Salt Phase Transition in LiNiO2 Cathode Material. Issue 25 (25th May 2020) - Ahmed, Shamail; Bianchini, Matteo; Pokle, Anuj; Munde, Manveer Singh; Hartmann, Pascal; Brezesinski, Torsten; Beyer, Andreas; Janek, Jürgen; Volz, Kerstin
Abstract: The layered oxide LiNiO2 (LNO) has been extensively investigated as a cathode active material for lithium‐ion batteries. Despite LNO's high gravimetric capacity, instability issues hinder its commercialization. It suffers from capacity loss during electrochemical cycling and is difficult to synthesize without defects. This is related to poor structural stability, leading to decomposition into the parent rock‐salt‐type oxide. In order to understand such phase transformations and to develop measures to inhibit them, the development of techniques able to image all atoms is crucial. In this study, the use of a fast, pixelated detector and 4D imaging in scanning transmission electron microscopy are explored to tackle this challenge. Selecting specific angular regions in the diffraction patterns and calculating virtual annular bright‐field images significantly enhances the contrast of the lithium atoms, such that all atoms are visible even in realistic samples. The developed technique is applied to image the layered‐to‐rock salt phase transition region. The data show that in this region, nickel atoms are in tetrahedral positions and the oxygen atoms are asymmetrically distributed. Taken together, the results shed light on the phase transformation mechanism at the atomic scale and can guide future research toward stabilizing LNO. Abstract : There are still issues that hinder LiNiO2 's commercialization. Using advanced 4D scanning transmission electron microscopy (4D STEM) all elements in the structure are imaged at atomic‐resolution and the contrast from light elements is enhanced. The process by which atoms change positions in the layered‐to‐rock salt phase‐transformation region is elucidated. The results are crucial to understand the underlying phase‐transformation mechanism.